Cigarette smoking and obesity are associated with decreased fat perception in women. (25th January 2014) - Pepino, Marta Yanina; Mennella, Julie A.
<x xml:space="preserve">Abstract</x> Objective Smoking and obesity are independently associated with high consumption of high‐fat foods in women. We tested whether the co‐occurrence of smoking and obesity associates with reduced oral fat perception. Methods Four groups of women (14 obese smokers, 11 obese never‐smokers, 10 normal‐weight smokers, 12 normal‐weight never‐smokers) rated vanilla puddings that varied in fat content for perceived intensity of creaminess and sweetness, using the general Labeled Magnitude Scale (gLMS), and degree of pleasantness, using the hedonic gLMS. To determine the role of retronasal smell, subjects rated puddings with and without noseclips. Results For all groups, perception of creaminess grew with increasing fat concentrations; puddings with any amount of fat were perceived as sweeter than fat‐free pudding, and sweetness was enhanced when tasted without noseclips. Overall, obese smokers perceived less creaminess, sweetness, and pleasure while tasting the puddings than did the other three groups (all P values < 0.02). Conclusion The ability to perceive fat and sweetness in and derive pleasure from foods is particularly compromised in obese women who smoke, which could contribute to excess calorie intake in this population already at high risk for cardiovascular and metabolic disease. Retronasal olfaction appears not to contribute to blunted flavor perception observed in obese smokers.